2016
DOI: 10.1111/cup.12666
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of lichenoid reactions in patients treated with anti‐PD‐L1 and anti‐PD‐1 therapy

Abstract: These findings expand the literature of immune-related toxicities of PD-L1 and PD-1 blockade to include lichenoid dermatitis and lichenoid mucositis. Of note, these cutaneous side effects were amenable to topical treatment, without the need for medication dose reduction or discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 13 publications
8
128
1
3
Order By: Relevance
“…In line with our report, Lindner et al [13], in 2009, reported the case of a metastatic renal cell carcinoma patient who developed an “immune-mediated” lichen ruber 6 months after starting nivolumab therapy. Later, various groups reported the occurrence of lichenoid lesion during anti-PD-1/anti-PD-L1 therapy [14, 15]. Additionally, in our patient the development of lichen ruber might be related to the infection with HCV, representing an important risk factor for this disease [16].…”
Section: Discussion/conclusionmentioning
confidence: 60%
“…In line with our report, Lindner et al [13], in 2009, reported the case of a metastatic renal cell carcinoma patient who developed an “immune-mediated” lichen ruber 6 months after starting nivolumab therapy. Later, various groups reported the occurrence of lichenoid lesion during anti-PD-1/anti-PD-L1 therapy [14, 15]. Additionally, in our patient the development of lichen ruber might be related to the infection with HCV, representing an important risk factor for this disease [16].…”
Section: Discussion/conclusionmentioning
confidence: 60%
“…These lesions generally occurred several months after treatment induction. Histopathology and immunophenotypic analysis of the lichenoid lesions associated with anti-PD1 and anti-PDL-1 therapy seem to reveal greater histiocytic infiltrate than that observed in similar nondrug-related lichenoid reactions (i.e., lichen planus, lichen planus-like keratoses) [172].…”
Section: Lichenoid Reactionsmentioning
confidence: 74%
“…Recently, more characteristic oral lesions with PD-1 or PD-L1 inhibitors have been described [20,38,171,172].…”
Section: Pigmentary Changesmentioning
confidence: 99%
See 2 more Smart Citations